A descriptive cross-sectional study to assess prevalence of mal-nutrition in children under five years age in rural community Bikaner, Rajasthan - Acharya, Rekha; Meena, Rattiram (International Journal Of Community Medicine And Public Health, 2017)
Background: Malnutrition among children below five years continues to be one of India major human development challenges. In spite of tremendous economic progress made in the last two to three decades. The objective of the study was to assess prevalence of mal-nutrition in children under five years age in rural community Bikaner, Rajasthan. Methods:The study was cross-sectional community based study. The study was conducted in village udairamsar in Bikaner rural. It is a Rural Health Training Centre Sardar Patel Medical College Bikaner. Under five year children with sample size of 657 was taken for study. Results: It was observed that out of 657 children, 367(55.86%) were males and maximum (22.83%) children were belong 48-59months age group. All three parameters of malnutrition i.e. wasting, underweight and stunting were more common in males (21.80%, 37.06%, and 29.16%respectively) than females (16.55%, 26.21% and 21.72% respectively). Highest proportion (25.19%) of wasting was found in age group 36-47 months followed by age 12 to 23 months (23.88%). Conclusions:Majority of under five children were malnourished and malnutrition common in males than females.